2016
DOI: 10.1530/edm-16-0007
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid lipomatosis in a 36-year-old patient with rheumatoid arthritis and a kidney transplant

Abstract: SummaryThyroid lipomatosis is a rare disease, as a total of 20 cases have been described in the literature. It is characterized by diffuse infiltration of the stroma by mature adipose tissue and by progressive growth that produces different degrees of compressive symptoms. Our aim is to present the case of a 36-year-old woman who consulted because of dyspnea caused by a multinodular goiter. She underwent surgery with the presumptive diagnosis of a malignant neoplasia, but the pathological examination of the su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
21
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(25 citation statements)
references
References 13 publications
1
21
0
3
Order By: Relevance
“…Physical examination usually shows a so , nontender goiter that is nodular or di use. In most cases, tests show normal thyroid function, but both hyperthyroidism and hypothyroidism have been described in a few patients, usually mild, like our case [7].…”
Section: Discussionsupporting
confidence: 49%
See 4 more Smart Citations
“…Physical examination usually shows a so , nontender goiter that is nodular or di use. In most cases, tests show normal thyroid function, but both hyperthyroidism and hypothyroidism have been described in a few patients, usually mild, like our case [7].…”
Section: Discussionsupporting
confidence: 49%
“…Until 2000, García-Villanueva et al referred 200-250 published cases [5]. In our review, we have only found 9 cases published in the last 10 years, all of them were associated with kidney disease (CKD), with or without kidney transplant: 3 of them were associated with familial Mediterranean fever [1,6], 2 cases were associated with rheumatoid arthritis [3,7], 1 case was associated with bronchiectasis [2], another case with bronchiectasis and ankylosing spondylitis [1], and other 2 cases were associated with Crohn's disease [4] and multiple myeloma [8] ( Table 1). Hijazi et al [9] reviewed four more cases of thyrolipomatosis until 2018, publishing a new case in a 53-year-old woman with renal failure secondary to diabetic nephropathy, without anatomopathological study for amyloid.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations